THE EFFECTS OF JOB DEMANDS AND JOB RESOURCES ON TURNOVER INTENTION AMONG MALAYSIAN TEACHERS: THE MEDIATING ROLE OF BURNOUT WITHIN THE JOB DEMANDS-RESOURCES (J-DR) MODEL - Md Shah, Suzita; Kamarul Zaman, Maliza Delima (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Turnover intention is the psychological readiness of employees when they leave their current role, which influenced by many factors like job satisfaction, workload and organizational support (Tetteh et al., 2022). Li and Yao (2022) in their study found that challenging student behaviors, poor school climate and insufficient compensation and other factors influenced teacher turnover. Rasanen et al. (2020) in the study found a job dissatisfaction plays a significant role in turnover intention. In addition, Rajendran et al. (2020) found a strong relationship between burnout and teacher turnover in their study. There is because of limited resources and workload. Positive work environment, offer support to the teachers and providing adequate resources in schools is needed to reduce turnover intentions among them. Therefore, this research shows high work demands, emotional distress and limited resources, a key predictor in numerous educational settings caused turnover intention. However, before this, most studies were only conducted outside Malaysia. This demonstrates the essential of investigating turnover intention in the local context, considering factors such as workload. work-life balance, work environment, perceived organizational support and job autonomy may have diverse influences on teachers’ turnover intention. In this study, teacher turnover intentions were the dependent variable. Turnover is recognized as a strong predictor impacting stability, efficiency and the educational system (Rajendran et al., 2020: Heffernan et al, 2022).